Inhibition of human neutrophil elastase by labdane diterpenes from the fruiting bodies of Ramaria formosa. Issue 12 (2nd December 2015) - Lee, Ik-Soo; Kim, Kwan-Chul; Yoo, Ick-Dong; Ha, Byung-Jo
Abstract: Two new labdane diterpenes (1 and 2 ) were isolated from the fruiting bodies of Ramaria formosa . The structures of these compounds were established by extensive spectroscopic studies and chemical evidence. The inhibitory activity of compounds 1 and 2 against human neutrophil elastase (HNE) was evaluated in vitro . Compounds 1 and 2 inhibited HNE activity moderately. The IC50 values for compounds 1 and 2 were 36.4 ± 1.2 and 40.8 ± 1.5 μM, respectively; the IC50 value for the positive control, EGCG, was 12.5 ± 0.8 μM. In addition, the mechanism by which 2 inhibited HNE was a mixed-type noncompetitive inhibition, with a K i of 41.5 ± 1.8 μM. Graphical abstract: :